The Sociology of Gambling: Review - Валерия Эдуардовна Волкова; Денис Олегович Стребков (Journal of Economic Sociology, 2011)
The article presents a review of literature in sociology of gambling. It focuses on the role played by the gambling in the lives of individuals and society. Classiﬁ cation of motives and typologies of gamblers are summarized along with the social and cultural underpinnings of gambling development and diffusion in contemporary societies. Special attention is paid to the state regulation of gambling in different countries, which became a subject of special interest since the federal law that banned gambling business in Russia came into force in 2009.